Behavior of hemoglobin concentration, hematocrit and oxygen saturation in Colombian university population at different altitudes (2015)
Introduction: the development of this research is base on the growing interest in understanding the adaptations to chronic hipoxia mainly in the range of intermediate altitudes (1 500-3 000 m.s.n.m) and the need to establish parameters of normality in the variables [Hb], Hct and SO2 for diagnostic and characterization of the population purposes. Objective: to analyze the behavior of the [Hb], Hct and SaO2 at different intermediate altitudes (970 m.s.n.m, 1 520 m.s.n.m, 1 728 m.s.n.m, 1 923 m.s.n.m, 2 180 m.s.n.m and 2 600 m.s.n.m) in order to contribute to the knowledge of the high altitude physiology and the clinical field to support the diagnosis of anemia. Methods: clinically healthy subjects with low levels of physical activity and food consumption report containing iron. Total of 264 participants of both genders between 18 and 30 years. The blood samples were collected from the antecubital vein and the earlobe and analyzed in a radiometer. A non-parametric statistical analysis was performed. Results: with increasing of altitude, [Hb] and Hct values were increased while the SO2 decreased. Men showed higher values than women in [Hb] and Hct, related to lower values of SO2 than women. Discussion: a threshold variable was not found, perhaps because of the small distance between the altitudes. The values reported were similar but not identical to other studies. This difference could be explained by genetic diversity among populations. Conclusions: this study allows for the first values of characterization of the study population. All altitudes were above the cutoff for the diagnosis of anemia ([Hb] 12 g/dl). © 2015, Grupo Aula Medica S.A. All rights reserved.